2022
DOI: 10.1002/ccd.30484
|View full text |Cite
|
Sign up to set email alerts
|

SCAI stage reclassification at 24 h predicts outcome of cardiogenic shock: Insights from the Altshock‐2 registry

Abstract: Background: Cardiogenic shock (CS) includes several phenotypes with heterogenous hemodynamic features. Timely prognostication is warranted to identify patients requiring treatment escalation. We explored the association of the updated Society for Cardiovascular Angiography and Interventions (SCAI) stages classification with in-hospital mortality using a prospective national registry. Methods: Between March 2020 and February 2022 the Altshock-2 Registry has included 237 patients with CS of all etiologies at 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…[22] On the other hand, data from the Altshock-2 Registry with 237 patients hospitalized with CS between 2020 and 2022 showed that the deteriorating rates in SCAI stages after 24 hours were 41%, 6.7%, 11.3% in patients were initially classified as stages B, C, and D, respectively. [23] Differences in the focused populations between our study and other studies prevent any direct comparison of the distribution and progression of SCAI shock stages. However, findings from our study suggest that most AMI patients presented to the hospital with either stable but at-risk conditions (SCAI stage A) or early shock stage (SCAI stage B), and these patients tended to remain stable in the next 24 hours.…”
Section: Scai Stages Distribution and Transitionmentioning
confidence: 82%
See 1 more Smart Citation
“…[22] On the other hand, data from the Altshock-2 Registry with 237 patients hospitalized with CS between 2020 and 2022 showed that the deteriorating rates in SCAI stages after 24 hours were 41%, 6.7%, 11.3% in patients were initially classified as stages B, C, and D, respectively. [23] Differences in the focused populations between our study and other studies prevent any direct comparison of the distribution and progression of SCAI shock stages. However, findings from our study suggest that most AMI patients presented to the hospital with either stable but at-risk conditions (SCAI stage A) or early shock stage (SCAI stage B), and these patients tended to remain stable in the next 24 hours.…”
Section: Scai Stages Distribution and Transitionmentioning
confidence: 82%
“…Several recent studies have shown that changes in the SCAI stage after 24 hours of access may also provide valuable prognostic information. [21][22][23] The present study aimed to describe the distribution at admission and transition of the SCAI stages and after 24 hours and their association with 30-day mortality in patients with AMI in a major referral center in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…However, most published studies examining the association between the SCAI Shock classification and mortality have assessed shock severity at a single time point, often including data from different periods during hospitalization (14)(15)(16)(17). Those few studies that have recorded the SCAI Shock classification more than once have typically assessed shock severity at admission followed by a repeat assessment at 24 h or determined the worst stage during hospitalization (18)(19)(20)27,28). These studies have generally observed that persistently high or increasing shock severity is associated with a worse outcome than decreasing shock severity.…”
Section: Introductionmentioning
confidence: 99%
“…Morici et al 3 in a recent original article reported in hospital mortality rates based on SCAI stage. They found a statistically significant higher rate of mortality in those with SCAI stage D and E at enrollment.…”
mentioning
confidence: 99%